Development of an IoT prototype for soil moisture monitoring in coffee farming - Rezende, Isadora Bernardo; Vilela, Flávio Fraga (Brazilian Journal of Production Engineering, 2026)
Technology has expanded efficiency in agriculture, however, in Brazil there is still a significant disparity between highly technified farms and those with low adoption of technological solutions. In this context, the present study presents the development of an Internet of Things (IoT)-based prototype for monitoring soil moisture in coffee plantations, with the objective of providing an accessible and viable solution to support irrigation management in precision agriculture. The prototype uses a resistive soil moisture sensor, a microcontroller, a display, and an IoT platform to measure, visualize, and transmit soil moisture data in real time. The system development followed the five phases of the product development process: concept, planning, engineering, testing, and prototyping. Initial tests were conducted in a controlled environment, in which the system showed consistent readings and immediate responses to variations in soil moisture. It is concluded that the IoT prototype presents potential as a low-cost solution to support real-time monitoring of soil moisture in coffee crops. For future studies, the use of solar energy, integration with long-range communication networks, improvements in the calibration process, and the application of artificial intelligence techniques are recommended.
Keywords: Precision Agriculture; Internet of Things (IoT); Real-Time Monitoring; Soil Moisture